Editorial of Special Issue “Metabolomic Analysis in Health and Diseases” - Sugimoto, Masahiro (Journal of Clinical Medicine, 2021)
Metabolomics, a quantitative omics technology that simultaneously profiles hundreds of metabolites, has been used to explore new biomarkers and elucidate the metabolic pathways perturbed by various stimuli at a system level [...]